Measuring fatigue crack growth and closure in Polyether Ether Ketone (PEEK). (February 2017) - Colmer, Tinsley; Daniewicz, S.R.; Newman, J.C.; Moser, Robert
Highlights: Crack growth data for 450G PEEK collected over 6 orders of magnitude. Crack growth is significantly affected by load ratio. Remote crack closure measurements are not sensitive enough to measure crack closure during the fatigue crack growth. Abstract: Throughout industry, polymers are being used to replace parts that were previously fabricated from metals. Thus, the fatigue resistance of polymers needs to be well understood. Polyether Ether Ketone (PEEK) is often chosen for its good mechanical properties and high glass transition temperature. In this paper, the experiments and methods to study fatigue crack growth and subsequent crack closure are presented. Compact specimens made of PEEK were used to experimentally monitor fatigue crack growth at R = 0.1 and R = 0.7. Some unique aspects of the experiments include the use of compression pre-cracking and a back-face strain gauge to measure crack length. While measuring crack closure was the primary focus of the experiments, crack growth rate versus stress intensity factor range results were also generated. Using remote methods of measuring crack closure show that PEEK experiences a small level of crack closure, though the effects are minimal. However, indirect methods of measuring crack closure show that the phenomenon is more prevalent in the material than what was measured. Further research for continuing the study of fatigue crack closure in PEEK are discussed.